Evaluating the Impact of Whole-Body Vibration (WBV) on Fatigue and the Implications for Driver Safety - Troxel, Wendy M. (RAND Corporation, 2015)
Summarizes the findings from RAND's review of the literature on whole-body vibration (WBV) and fatigue and also considers appropriate study designs and methodologies to inform new areas of research focused on the impact of WBV on fatigue with the goal of improving the safety of truck drivers. Identifies 24 studies examining the impact of WBV on fatigue or sleepiness. Recommendations for future studies to strengthen the evidence base are included.